Audiology practice in assessing and managing tinnitus: a cross-sectional study - Alkahtani, Rania; Alshamardel, Aryam; Alzakari, Asma; Alshaya, Rahaf; Aldawsari, Sarah; Aldawsari, Haya; Frhan, Haya; Elbeltagy, Reem (Frontiers in Neurology, 2025)
ObjectivesTinnitus may negatively impact quality of life, emphasizing the importance of effective management to support patients’ well-being. This study aimed to gain insights into the current practices among audiologists in Saudi Arabia in assessing and managing tinnitus patients and to identify areas for improvement.MethodsA cross-sectional study surveyed 96 audiologists using an electronic questionnaire comprising 30 items and 5 demographic questions. The questionnaire covered appointment structure, tinnitus assessment and management, outcome measures, determinants of successful management, clinical skills, resource availability, and satisfaction with services.ResultsOnly 14.6% of workplaces had specialized tinnitus clinics, and appointment durations were generally short. Of the audiologists, 32.3% reported practicing multidisciplinary care, while group therapy was not used, and family involvement was acknowledged by less than half. Audiological tests were widely used for assessment, but psychoacoustic measures and validated questionnaires were uncommon. Management primarily relied on hearing aids and counseling, with limited use of psychological approaches such as cognitive behavioral therapy. Audiologists reported moderate satisfaction with their effectiveness in managing tinnitus (mean = 3.25 ± 0.98). Higher satisfaction was associated with working in specialized clinics, multidisciplinary teams, same-day assessment and treatment, and more trained audiologists available for counseling (all p < 0.05). However, none of these factors remained significant in regression analysis.ConclusionTinnitus practice in Saudi Arabia revealed notable discrepancies in approaches taken by audiologists, primarily due to limited training and resources. Establishing evidence-based guidelines, expanding professional training, and improving resource allocation are needed to enhance the quality and consistency of tinnitus care, ultimately improving patient outcomes.